The Effect of the Creative Problem Solving (CPS) Learning Model on Students’ Creative Thinking Skills in Learning about the Effects of Hydrocarbon Combustion - Ratna Sari Siti Aisyah; Pepi Nurul Jannah; Lusiani Dewi Assaat (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
Students’ creative thinking skills in chemistry learning remain relatively low, particularly on the topic of the impacts of hydrocarbon combustion. Therefore, an effective learning model is needed to enhance these skills. This study offers a specific contribution by examining the implementation of the Creative Problem Solving (CPS) learning model in the context of hydrocarbon combustion, a chemistry topic closely related to real-life environmental issues and requiring students to generate original and relevant solutions. This study was conducted to identify the differences in students’ creative thinking skills before and after the implementation of the CPS learning model, as well as to examine the extent of improvement following its implementation. The study employed a pre-experimental method using a one-group pretest–posttest design. The participants were 37 students from class XI-2 of SMAN 3 Serang City, selected through purposive sampling. The findings revealed a significant difference in students’ creative thinking skills before and after the implementation of the CPS learning model, as indicated by a sig. (2-tailed) value of 0.000 (< 0.05). The students’ average score increased from 28% to 76%, while the N-gain results showed a moderate to high level of improvement. These results indicate that the CPS learning model was effective in improving students’ creative thinking skills and provides empirical support for its use in contextual chemistry learning, particularly on environmental topics such as hydrocarbon combustion.